2021
DOI: 10.1021/acssuschemeng.1c05238
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Assembly to Simultaneously Heterogenize Polyoxometalates as Nanozymes and Encapsulate Enzymes in a Microstructure Endowing Efficient Peroxidase-Mimicking Activity

Abstract: A polyamine-mediated bioinspired strategy to assemble polyoxometalate (POM) [phosphotungstic acid (PTA)/ phosphomolybdic acid (PMA)] nanoclusters and glucose oxidase (GOx) generating microsphere structures under very mild reaction conditions is demonstrated. The noncovalent interactions between multivalent anions (citrate ions) and polyamine chains [poly-(allylaminehydrochloride), PAH] are key to the assembly process, which results in positively charged coacervates, allowing the assembly of GOx and POM nanoclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In addition, the catalytic activity of nanozymes is also related to nanoscale factors, such as their size, morphology and surface, which significantly affect their activity. Nayak et al [ 44 ] assembled polyoxometalate (POM) (phosphotungstic acid (PTA)/phosphomolybdic acid (PMA)) nanoclusters and glucose oxidase (GOx) into microsphere structures, which facilitated the better diffusion of the reactants, intermediates and products due to the small size of the microspheres. This resulted in a 3–5-fold increase in the peroxidase-like activity of the PTA nanoclusters in the nanozyme microspheres.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the catalytic activity of nanozymes is also related to nanoscale factors, such as their size, morphology and surface, which significantly affect their activity. Nayak et al [ 44 ] assembled polyoxometalate (POM) (phosphotungstic acid (PTA)/phosphomolybdic acid (PMA)) nanoclusters and glucose oxidase (GOx) into microsphere structures, which facilitated the better diffusion of the reactants, intermediates and products due to the small size of the microspheres. This resulted in a 3–5-fold increase in the peroxidase-like activity of the PTA nanoclusters in the nanozyme microspheres.…”
Section: Resultsmentioning
confidence: 99%
“…Figure C shows a linear increase in the absorbance at 652 nm over a range of 0–500 μM glucose concentrations with a slope of 1.1 × 10 –3 μmol –1 L. The estimated LOD of glucose is 272 nM, which is superior or comparable to most of the previously reported nanozymatic systems (Table S1). Earlier, Rana and co-workers fabricated a bioinspired coacervate assembly using polyallylamine and citrate ions and demonstrated efficient peroxidase-mimicking activity of surface-anchored polyoxometalate (POM) nanoclusters with a LOD of 0.31 mM for glucose . Our estimated LOD is dependent on the solution pH and the present system shows the highest sensitivity at pH = 6 (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, Rana and co-workers fabricated a bioinspired coacervate assembly using polyallylamine and citrate ions and demonstrated efficient peroxidase-mimicking activity of surface-anchored polyoxometalate (POM) nanoclusters with a LOD of 0.31 mM for glucose. 57 Our estimated LOD is dependent on the solution pH and the present system shows the highest sensitivity at pH = 6 (Figure 8D). These spectral changes are accompanied by a gradual color change of the solution from colorless to blue as a function of glucose concentrations (Figure 8E, upper panel).…”
Section: Selective Glucose Sensingmentioning
confidence: 99%
“…Understanding the redox activity of POMs toward proteins is of crucial importance since different studies have suggested that the redox properties of POMs are responsible for their antibacterial and antitumor activity. , For example, the observed reduction of K 6 [P 2 W 18 O 62 ]·14H 2 O and K 4 [SiMo 12 O 40 ]·3H 2 O in Gram-positive drug-resistant bacteria is an indication of their ability to penetrate through the cell wall and interfere with the electron transfer system of the cell, making these POMs effective antibacterial agents . Furthermore, the ability of POMs to oxidize biological substrates through activating H 2 O 2 , which is akin to the reactivity of peroxidase enzymes, has enabled their development as biosensors for the detection of H 2 O 2 – such as in colorimetric immunoassays for cancer cells–and as catalysts for the degradation of dye pollutants in water. , Therefore, the multiple emerging biological and medical applications of POMs incite studying the redox chemistry of POMs toward biomolecules. ,, …”
Section: Redox Activitymentioning
confidence: 99%